The effectiveness of eating-based mindfulness training on emotional processing and self-differentiation of overweight women - Shariati, Sahar; Abbasi, Ghodratollah; Mirzaian, Bahram (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The aim of this study was to determine the effectiveness of eating-based mindfulness training on emotional processing and self-differentiation of overweight women. Method: The design of the present study was a quasi-experimental type of pre-test, post-test and follow-up with a control group. The statistical population in this study included all overweight women in Gonbad Kavous who in the first half of 2021 referred to overweight and obesity treatment clinics in this city. From the statistical population of the study, a sample group consisting of 30 overweight women who were purposefully selected and then randomly assigned to two experimental groups (eating-based mindfulness training) (n = 15) and control (n = 15). Were. The overweight women in the experimental group then underwent 8 sessions of 90 minutes per week of one MB-EAT training session, but the control group did not receive any intervention. The research instruments were emotional processing questionnaires (Baker et al., 2007) and self-differentiation questionnaire (Skowron and Friedlander, 1988). Analysis of variance with repeated measures and SPSS software were used to analyze the data. Results: The results showed that there was a significant difference between the subjects in the experimental group in terms of improving repression, unpleasant emotional experience, emotional symptoms of processing, avoidance, emotional control, emotional reaction, my position, emotional cutting and fusion with others. Was with the control group (P<0.01). Conclusion: It can be concluded that eating-based mindfulness training was effective on emotional processing and differentiation of overweight women and this effect continued until the follow-up period.